The implementation of Electronic Medical Record (EMR) in hospitals / Wan Nor Syazana Wan Hashim - Wan Hashim, Wan Nor Syazana; Jislan, Fatanah; Mohd Kodri, Aida Nur; Eshak, Erratul Shela; Mohd Nor, Khalijah; Nor Azam, Noor Haty (2023)
The trend of electronic medical records (EMR) was on a steady rise worldwide. Governments and healthcare authorities worldwide have been promoting the use of EMRs to improve patient care, data management, and healthcare efficiency. However, implementing electronic medical records (EMR) systems, while beneficial in the long run, can present several challenges for healthcare organizations including the initial cost involved in acquiring the software, hardware, and infrastructure necessary to support the system. Thus, the aim of this study is to conceptualized the practices that are being utilized by Electronic Medical Records (EMR) systems in hospitals. The current study involves reviewing research articles which were gathered from Scopus, ScienceDirect and a few other online databases. This study discussed the implementation, benefits, and challenges of EMRs by conducting a complete literature review. Based on the findings, previous studies prove that EMRs implementation significantly improve the quality of healthcare, the results for patients, and the security of patient data. This study does not involve any systematic literature search however, the selection of articles is strictly limited to the established online databases. Healthcare organizations should consider ongoing support and continuous improvement efforts to maximize the benefits of EMR systems while mitigating potential issues. The research sheds light on the obstacles that are faced during EMR integration and identifies potential opportunities for development. It is essential to have an understanding of EMR practices in hospitals in order to maximize the efficiency of healthcare information management and improve the standard of healthcare provided throughout the country of Malaysia.